Mental Capacity under the English Mental Capacity Act: An Analytical Study - Fayyad , Mahmoud; Alnazer, Raneen (Journal of Legal Sciences, 2025)
This study presents a descriptive and analytical examination of the English Mental Capacity Act 2005, one of the most significant legislative instruments concerned with protecting individuals who experience mental impairment while preserving their legal autonomy. The Act is founded on a core principle: capacity is presumed in every person, and it may only be rebutted through an objective assessment demonstrating an inability to understand, appreciate, or make a decision. The research seeks to analyze the legal and philosophical framework underpinning this legislation, highlighting how it strikes a careful balance between legal protection and individual freedom. Using a descriptive–analytical approach, the study examines relevant statutory and doctrinal texts, alongside judicial applications that have helped consolidate the notion of mental capacity as a functional and situational concept, rather than a fixed or permanent mental condition. The findings reveal that the Mental Capacity Act represents a fundamental shift in English legal thought, embodying a human-centered approach that promotes a more balanced and dignified understanding of capacity, reason, and personhood. This model could serve as an inspiring foundation for the future development of other legal systems seeking to reconcile protection with autonomy in a humane and equitable manner.